Riemannian geometry - Gallot, Sylvestre; Hulin, Dominique; Lafontaine, Jacques (Heidelberg: Springer, 2004)
Traditional point of view: pinched manifolds 147 Almost flat pinching 148 Coarse point of view: compactness theorems of Gromov and Cheeger 149 K. CURVATURE AND REPRESENTATIONS OF THE ORTHOGONAL GROUP Decomposition of the space of curvature tensors 150 Conformally flat manifolds 153 The second Bianchi identity 154 CHAPITRE IV : ANALYSIS ON MANIFOLDS AND THE RICCI CURVATURE A. MANIFOLDS WITH BOUNDARY Definition 155 The Stokes theorem and integration by parts 156 B. BISHOP'S INEQUALITY REVISITED 159 Some commutations formulas Laplacian of the distance function 160 Another proof of Bishop's inequality 161 The Heintze-Karcher inequality 162 C. DIFFERENTIAL FORMS AND COHOMOLOGY The de Rham complex 164 Differential operators and their formal adjoints 165 The Hodge-de Rham theorem 167 A second visit to the Bochner method 168 D. BASIC SPECTRAL GEOMETRY 170 The Laplace operator and the wave equation Statement of the basic results on the spectrum 172 E. SOME EXAMPLES OF SPECTRA 172 Introduction The spectrum of flat tori 174 175 Spectrum of (sn, can) F. THE MINIMAX PRINCIPLE 177 The basic statements VIII G. THE RICCI CURVATURE AND EIGENVALUES ESTIMATES Introduction 181 Bishop's inequality and coarse estimates 181 Some consequences of Bishop's theorem 182 Lower bounds for the first eigenvalue 184 CHAPTER V : RIEMANNIAN SUBMANIFOLDS A. CURVATURE OF SUBMANIFOLDS Introduction 185 Second fundamental form 185 Curvature of hypersurfaces 187 Application to explicit computations of curvature 189 B. CURVATURE AND CONVEXITY 192 The Hadamard theorem C.
I: Differential Manifolds -- A. from Submanifolds to Abstract Manifolds -- B. Tangent Bundle -- C. Vector Fields: -- D. Baby lie Groups -- E. Covering maps and Fibrations -- F. Tensors -- G. Exterior forms -- H. Appendix: Partitions of Unity -- II: Riemannian Metrics -- A. Existence Theorems and first Examples -- B. Covariant Derivative -- C. Geodesics -- III: Curvature -- A. the Curvature Tensor -- B. first Second Variation of arc-Length and Energy -- C. Jacobi Vector Fields -- D. Riemannian Submersions and Curvature -- E. The Behavior of Length and Energy in the Neighborhood of a Geodesic -- F. Manifolds with Constant Sectional Curvature -- G. Topology and Curvature -- H. Curvature and Volume -- I. Curvature and Growth of the Fundamental Group -- J. Curvature and Topology -- K. Curvature and Representations of the Orthogonal Group -- Chapitre IV: Analysis on Manifolds and the Ricci Curvature -- A. Manifolds with Boundary -- B. Bishop's Inequality Revisited -- C. Differential forms and Cohomology -- D. Basic Spectral Geometry -- E. Some Examples of Spectra -- F. The Minimax Principle -- V. Riemannian Submanifolds.
Keywords: Mathematics; Global differential geometry; Cell aggregation -- Mathematics; Mathematical physics; Mathematics; Differential Geometry; Manifolds and Cell Complexes (incl. Diff.Topology).; Mathematical Methods in Physics; Numerical and Computational Physics